Lifestyle, efficiency and limits: modelling transport energy and emissions using a socio-technical approach - Brand, C; Anable, J; Morton, C (Springer Netherlands, 2018)
It is well-known that societal energy consumption and pollutant emissions from transport are influenced not only by technical efficiency, mode choice and the carbon/pollutant content of energy but also by lifestyle choices and socio-cultural factors. However, only a few attempts have been made to integrate all of these insights into systems models of future transport energy demand or even scenario analysis. This paper addresses this gap in research and practice by presenting the development and use of quantitative scenarios using an integrated transport-energy-environment systems model to explore four contrasting futures for Scotland that compare transport-related ‘lifestyle’ changes and socio-cultural factors against a transition pathway focussing on transport electrification and the phasing out of conventionally fuelled vehicles using a socio-technical approach. We found that radical demand and supply strategies can have important synergies and trade-offs between reducing life cycle greenhouse gas and air quality emissions. Lifestyle change alone can have a comparable and earlier effect on transport carbon and air quality emissions than a transition to EVs with no lifestyle change. Yet, the detailed modelling of four contrasting futures suggests that both strategies have limits to meeting legislated carbon budgets, which may only be achieved with a combined strategy of radical change in travel patterns, mode and vehicle choice, vehicle occupancy and on-road driving behaviour with high electrification and phasing out of conventional petrol and diesel road vehicles. The newfound urgency of ‘cleaning up our act’ since the Paris Agreement and Dieselgate scandal suggests that we cannot just wait for the ‘technology fix’.